Izzivi polja ljubiteljskega gledališča v Estoniji - Saro, Anneli (Amfiteater (Ljubljana), 2020)
The article aims to present the first results of the first phase of the amateur theatre study conducted throughout Estonia in 2019 and to compare the results with the field of professional theatre. The article is divided into four parts. First, the authors introduce the methodology of the research. In the second part, they give a statistical overview of Estonian amateur theatre. After that, they compare the political strategies implemented in professional and amateur theatres. Finally, they introduce the biggest challenges of amateur groups and potential solutions. Out of approximately 200 adult amateur theatres, 85 (43%) answered the questionnaire. Of those Estonian amateur theatres responding, 39% is a part of a larger organisation, usually a local cultural house. A few (29%) operate as NGOs, or they have no legal status (28%). 65% of the theatres receive regular funding, but many of them and almost all the others apply for project-based funding also. The most important funding body is local municipalities, which support 79% of the theatres. The highest cost items are transport and workshops. Estonian amateur theatres produce mostly spoken theatre. Festivals play a crucial role in the amateur theatre field, and most of the theatres attend festivals regularly. The three most significant challenges of amateurs are related to membership issues, repertoire and funding.
Keywords: amateur theatre; challenges of amateurs; cultural policy; Estonian theatre; estonsko gledališče; izzivi amaterjev; kulturna politika; ljubiteljsko gledališče; STEP